EFEKTIVITAS MEDIA SOSIAL TIKTOK SEBAGAI ALAT KAMPANYE PARTAI POLITIK - Hamman Satyagraha, Muhamad; Mulyana, Dadang; Cahyono, Cahyono (Triwikrama: Jurnal Ilmu Sosial, 2025)
Abstract This study is entitled The Effectiveness of TikTok Media Social as a Political Party Campaign Tool (Case Study of Ciborelang Village, Jatiwangi District, Majalengka Regency). This study aims to determine the effectiveness of the role of TikTok social media as a political campaign tool in Ciborelang Village, Jatiwangi District, Majalengka Regency. With a qualitative approach and the method used is a case study. The subjects in this study were the related parties in Ciborelang Village, Jatiwangi District, Majalengka Regency. The results of this study indicate that: (1) Political party campaign content to gain public attention in an effort to win the general election contest is a way for political parties to utilize social media such as TikTok in conveying information related to the vision, mission, and work programs of their cadres through content such as short videos, podcasts, and recordings of socializations that are packaged creatively to make them more interesting and easy to digest; (2) TikTok social media has a role and function as a tool to convey visions, missions, and work programs digitally and this also allows messages to be conveyed quickly and efficiently thanks to features such as For You Page (FYP); (3) The effectiveness of TikTok social media as a political party campaign tool is an assessment of TikTok social media itself regarding how important and impactful digital media is in efforts to win political candidates (in this case political party cadres) in general election contests, especially in Majalengka Regency. Keywords: Effectiveness, TikTok Media Social, Political Campaign. Abstrak Penelitian ini berjudul Efektivitas Media Sosial TikTok Sebagai Alat Kampanye Partai Politik (Studi Kasus Desa Ciborelang, Kecamatan Jatiwangi, Kabupaten Majalengka). Penelitian ini bertujuan untuk mengetahui efektivitas peran media sosial TikTok sebagai alat kampanye politik di Desa Ciborelang, Kecamatan Jatiwangi, Kabupaten Majalengka. Dengan pendekatan kualitatif dan metode yang digunakan yaitu studi kasus. Subjek dalam penelitian ini yaitu pihak-pihak terkait yang ada di Desa Ciborelang, Kecamatan Jatiwangi, Kabupaten Majalengka. Adapun hasil dari penelitian ini menunjukkan bahwa: (1) Konten kampanye partai politik guna mendapatkan atensi masyarakat dalam upaya memenangkan kontestasi pemilihan umum adalah cara partai politik memanfaatkan media sosial seperti TikTok dalam menyampaikan informasi terkait visi, misi, dan program kerja para kadernya melalui konten seperti video pendek, podcast, dan rekaman sosialisasi yang dikemas secara kreatif agar lebih menarik dan mudah dicerna; (2) Media sosial TikTok memiliki peran dan fungsi sebagai alat untuk menyampaikan visi, misi, dan program kerja secara digital serta hal ini juga memungkinkan pesan tersampaikan secara cepat dan efisien berkat fitur seperti For You Page (FYP); (3) Efektivitas media sosial TikTok sebagai alat kampanye partai politik merupakan suatu penilaian terhadap media sosial TikTok itu sendiri terkait seberapa penting dan berdampak kah media digital dalam upaya memenangkan calon politisi (dalam hal ini kader partai politik) dalam kontestasi pemilihan umum, khususnya di Kabupaten Majalengka. Kata kunci: Efektivitas, Media Sosial TikTok, Kampanye Politik.